Cell-mediated and humoral immunity of choroidal melanoma patients after treatment with photocoagulation combined with strontium-90/yttrium-90 therapy versus transpupillary thermotherapy combined with strontium-90/yttrium-90 therapy - D.A. Drumi; S.I. Poliakova; L.M. Velychko; M.B. Makarova; I.V. Tsukanova; O.V. Bogdanova (Journal of Ophthalmology)
Purpose: To compare cell-mediated and humoral immunity characteristics of patients with T1 to T3 CM treated with photocoagulation (PC) combined with strontium-90 (Sr90)/ yttrium-90 (Yt90) brachytherapy (BT)) versus transpupillary thermotherapy (TTT) combined with Sr90/Yt90 BT.